Address to the Bankers' Club, London - Wolfensohn, James D. (World Bank, Washington, DC, 2017)
James D. Wolfensohn, President of the World Bank, made points on topics that link banking to the developing world: scourge of acquired immune deficiency syndrome (AIDS), which has 16 million people suffering from that disease; crime; war; migration, because migration comes from countries that do not have economic opportunity; and trade. It is crucial that the bankers in the city, as the home of international banking and the largest center of international banking, recognize that there is something more than the profit motive. As far as development is concerned, it's no longer an issue of having government to government assistance. $230 billion of private capital went to the developing world, eclipsing the $50 billion of official aid. International institutions have to change. And private institutions have to change in thinking not just of themselves but of leveraging their activities and their interests to work in partnership with the governments.